ปัจจัยที่มีผลต่อพฤติกรรมการบริโภคอาหารเพื่อสุขภาพของผู้บริโภคในอำเภอเมือง จังหวัดเชียงใหม่ - พิมพ์ใจ สิงคราช (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The present study aimed to understand consumption behavior toward foods for health and discern the factors influencing health food consumption among consumers in Mueang District of Chiang Mai Province. The needed information was collected by means of questionnaire from 200 samples each of individuals consuming health foods and those not consuming, covering 400 samples in total. The analysis was performed upon the results of Binary Choice Logit Model estimation. On consumption behavior toward foods for health, the investigation revealed that there were three most popular natures of diet for health concerns namely strict vegetarian or vegan, vegetarian, and natural and organic foods, in descending order. Consumers of health foods in all three forms were similarly found to have their healthy meals according to their belief and preference 1 – 2 times per week, but not to be definite about when in a day or a week they would do so. They also commonly learnt about health foods from books, magazines, and health related journals. On health food expenditure, most natural and organic food consumers spent no more than 100 baht per person per meal while vegetarians and vegans spent in the range of 101 – 200 baht. In terms of consumption habit, consumers of vegetarian foods appeared to have been on vegetarian diet for the longest time or more than 5 years compared with those vegans and natural and organic food consumers that have adhered to their current dietary preference for 3 – 4 years only. The inquiry into factors influencing consumers to adhere or turn to foods for health revealed that consumers in all three healthy food categories under study did so for their most important reason in the culture and tradition factor namely the doctrine that humans can live without exploiting animals and thus can abstain from eating animal products. The least influential was the social and economic factor as the consumers were introduced or persuaded to consume health foods by their colleagues at workplace or by their organizations. The regression model adopted for the present study appeared to have 82.25 % predictive accuracy in identifying factors which will influence the consumers’ choice to be in favor of health food consumption in the future. The most influential factors at 99 % statistically significant level for consumers to decide to consume health foods in the future were found to include gender, male age, education, occupation, personal health status, and the desire to heal or alleviate their ailments with the aid of health foods in the future. The Binary Choice Logit Model was applied for analysis on two groups of health food consumer: the vegans and non vegans. The results of this model estimation were able to explain the factors influencing the choice of consumers to consume health foods with 75.00 % predictive accuracy. At 99 % statistically significant level, the factors encouraging consumers to consume health foods were the desire to utilize healthy foods for healing or relieving the sickly symptoms of ailments, and the belief in and attitude toward the claim that eating healthy foods will be good and beneficial for one’ health and physical conditions as well as will help prevent certain diseases. Meanwhile, the explanatory factor at 95 % statistically significant level was male.